2010
DOI: 10.1007/s00167-010-1162-9
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of tunnel positions in single-bundle anterior cruciate ligament reconstructions using computer navigation

Abstract: Recurrent rotational instability has been identified as a potential source of failure of anterior cruciate ligament (ACL) reconstructions. The aim of the study was to assess whether knee kinematics in the horizontal configuration more closely resemble the intact knee when compared with other single-bundle configurations. Using the Praxim computer navigation system, ACL reconstructions were performed with tibialis anterior grafts in six fresh-frozen whole lower extremity cadaver specimens (12 knees). In each kn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
44
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(48 citation statements)
references
References 36 publications
(63 reference statements)
2
44
2
Order By: Relevance
“…Placement of the tunnels in these positions created grafts that were more vertically oriented in the sagittal and coronal planes than the native ACL, which is known to negatively impact the biomechanical function of the graft. [14][15][16][17][18] These findings are in agreement with a previous study that used similar MRI-based modeling techniques to measure 3D, subject-specific femoral graft placement, and found that a traditional transtibial technique typically placed grafts about 5 mm anterior and superior to the native ACL center. 37 Another study 22 used CT-based models to evaluate 3D tibial and femoral graft position after conventional transtibial reconstruction and found graft positions consistent with the current study, however, the positions were not evaluated on a patientspecific basis due to the limitations visualizing soft tissue in the contralateral knee with CT imaging.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Placement of the tunnels in these positions created grafts that were more vertically oriented in the sagittal and coronal planes than the native ACL, which is known to negatively impact the biomechanical function of the graft. [14][15][16][17][18] These findings are in agreement with a previous study that used similar MRI-based modeling techniques to measure 3D, subject-specific femoral graft placement, and found that a traditional transtibial technique typically placed grafts about 5 mm anterior and superior to the native ACL center. 37 Another study 22 used CT-based models to evaluate 3D tibial and femoral graft position after conventional transtibial reconstruction and found graft positions consistent with the current study, however, the positions were not evaluated on a patientspecific basis due to the limitations visualizing soft tissue in the contralateral knee with CT imaging.…”
Section: Discussionsupporting
confidence: 90%
“…[4][5][6] Observations of alterations in tibiofemoral kinematics following ACL reconstruction [7][8][9] have lead some authors to suggest that restoration of normal kinematics may play an important role in preventing premature OA in this population. [10][11][12][13] Interestingly, several recent cadaveric [14][15][16] and in vivo 17,18 studies have linked altered joint mechanics to reconstruction techniques that fail to place the graft within the footprint of the native ACL, thereby changing the orientation and corresponding biomechanical function of the ACL. Nonetheless, recent studies suggest that placement of grafts in a nonanatomic position is a frequent problem, with grafts commonly placed in a relatively vertical orientation in both the sagittal and coronal planes.…”
mentioning
confidence: 99%
“…Computer-assisted ACL reconstruction has been used to evaluate tunnel positioning (Nakagawa et al 2008;Voos et al 2010). Its use in evaluating knee kinematics and laxity is also valuable.…”
Section: Computer-assisted Surgery and Kinematicsmentioning
confidence: 99%
“…The existence of this technology allows for the objective reporting of physical examination components and helps to shape clinical practice and operative strategies toward individualized patient outcomes. Specifically, the in vitro simulation of the pivot shift test typically includes application of valgus and internal rotation torques to the knee, and the resulting anterior tibial translation is reported as the primary outcome [19,24,25]. Several different clinical tools have been utilized to objectively report real-time subject kinematics in the clinical and operative settings.…”
Section: Basic Theory Of Clinical Knee Biomechanics and Objective Assmentioning
confidence: 99%